أثر التحليل الاستراتيجي على الخيارات الاستراتيجية التنافسية للمنشآت الدوائية السورية - ناصر محمد جودت; حمود أحمد (Latakia University Journal - Economic and Legal Sciences Series, 2013)
تتمحور هذه الدراسة حول دراسة وتحليل العوامل البيئية التي تعد الركيزة الأساسية في تحديد واختيار الاستراتيجية المناسبة، حيث يتوقف نجاح الاختيار الاستراتيجي للمنشأة على نتائج التحليل الاستراتيجي لكل من بيئتها الداخلية والخارجية، وعليه فالمنشآت الدوائية أسوة بغيرها من المنشآت يجب أن تنتهج الفكر الاستراتيجي انطلاقاً من التحليل الاستراتيجي لبيئتها الداخلية والخارجية للوصول إلى نقاط القوة والضعف في بيئتها الداخلية واكتشاف الفرص والتهديدات التي تعيق عمل المنشأة في بيئتها الخارجية وأن تحدد خياراتها الاستراتيجية بناء على استغلال الفرص ونقاط القوة ومواجهة التهديدات ونقاط الضعف، بما يعزز قدرتها التنافسية ويضمن لها البقاء والنمو في السوق، وخصوصاً أن الصناعة الدوائية صناعة تنافسية بامتياز. واستنادا" الى ما تقدم تركّز البحث حول دراسة أهم النقاط المتعلقة بمفهوم البيئة الداوئية ومكوناتها ، والتحليل الاستراتيجي للبيئة الدوائية وأهميته وأساليبه وطرائقه بالإضافة إلى أثره في تحقيق الميزة التنافسية للمنشآت الدوائية كما أنه يركز في جانبه العملي على واقع عملية التحليل البيئي في منشآتنا الدوائية، وأهم مواضع النقص والقصور فيها، ويخلص إلى مجموعة من النتائج الهامة التي تم التوصل إليها من خلال الدراسة العملية وعلى رأسها تركيز منشآتنا الدوائية على تقييم وتحليل بعض جوانب الأداء الداخلي وعدم التركيز على تحليل مكونات البيئة الخارجية، بالإضافة إلى عدم فعالية عملية التحليل البيئي الذي تقوم به منشآتنا الدوائية في تحديد الخيار الاستراتيجي الذي يحقق الميزة التنافسية لها، ويقدم مجموعة من المقترحات والتوصيات التي من شأنها التي تسهم في تطويع عملية التحليل البيئي في منشآتنا الدوائية بما يمكنها من تبني خيارات استراتيجية ناجحة وفعالة وقادره على تحقيق الميزة التنافسية لها. The present study focuses on studying and analyzing the environmental elements which are considered the mainstay in determining and choosing the appropriate strategy, since the success of strategic choice of the establishment depends on the results of the strategic analysis of both its internal and external environment. Based on this, pharmacological organizations, like other organizations, should pursue the strategic thought, starting from strategic analysis of its internal and external environment so that it could discover the strengths and weaknesses in its internal environment, detect opportunities and threats that hinder the organization’s work in its external environment, and determine its strategic choices in accordance with investing choices and strengths and challenging threats and weaknesses to the extent that it could boost its competitiveness and ensure both its survival and development in the market, especially that pharmacological industry is such a supreme competitive industry. By virtue of the above mentioned, the research has focused on considering the most important issues related to the concept and constituents of pharmacological environment, importance, tactics and methods of strategic analysis of pharmacological environment, in addition to its effect on achieving the competitive character of pharmacological companies. Furthermore, it focuses, in its scientific side, on the reality of the process of environmental analysis in our pharmacological establishments, and the most important areas of shortage and insufficiency in them. Many significant results are concluded by the research. They are concluded through the practical study on the top of which is the fact that our pharmacological establishments do focus and concentrate on estimating and analyzing some sides of internal performance, but they do not focus on analyzing the constituents of external environment. Further, the process of environmental analysis, conducted by our pharmacological establishments in determining the strategic choice that could achieve their competitive character and offer a set of proposals and recommendations that may contribute to yielding of process of environmental analysis in our pharmacological establishments to the extent that they could adopt active and successful strategic choices capable of achieving their competitive character, is ineffective.